EVALUASI PELAKSANAAN DAN KEPUASAAN KLIEN PROVIDER INITIATED HIV TESTING AND COUNSELING (PITC) DI BBKPM SURAKARTA - Julia Pertiwi; Intan Zainafree (Dian Nuswantoro Semarang, 2016)
Provider Initiated HIV Testing and Counseling (PITC) at BBKPM Surakarta formed of collaboration to avaoid TB-HIV. The purpose of this study was to known the implementation of PITC and satisfaction of client of BBKPM Surakarta. This research was qualitative descriptive with an evaluation study design. The information collected from PITC program holder and PITC clients. The instruments of this research were structured interview guidelines, indepth interview guidelines, focus group discussions guidelines, observation and documentation. The results showed that PITC input indicator appropriated by guidelines. Process indicator, service procedures was appropriate guidelines. There were some interference, double responsible position, counseling must paid and CST holder insufficiently. Output indicator, targets PITC targets was unreached, form reports as appropriate guidelines and client satisfy with score 75,38%. The advices can be given were redesigning counseling room, adding PITC’s room keeper and CST holder, intern discussion among all BBKPM services and providing suggestion box.Keywords: Evaluation; PITC